Effects of a Bacillus-Based Feed Additive in Nursery Pig Diets Containing Low or High Levels of Soybean Meal - Ty H. Kim; Grady A. Privett; Pau Salgado-Lopez; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; Katelyn N. Gaffield; Thomas E. Weber; Kale Causemaker; Brooke Anderson; Dwight J. Shawk; et al. (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 4,320 nursery pigs (PIC 337 × 1050, initially 14.7 ± 0.21 lb) were used in a 42-d study to determine the effects of a bacillus-based feed additive on growth performance and fecal dry matter (DM) in nursery pig diets with low or high levels of soybean meal (SBM). At approximately 21 d of age, pigs were weaned, blocked by initial BW and allotted to one of four dietary treatments in a randomized complete block design with 20 replications per treatment. Diets were formulated in three phases and fed from d 0 to 7, 7 to 21, and 21 to 42, respectively. The four treatments were arranged in a 2 × 2 factorial with main effects of bacillus-based feed additive (none or 106 colony-forming units (CFU)/g of complete feed; Argis, Kent Nutrition Group, Muscatine, IA) and SBM level (low or high). On approximately d 14 (range of 9 to 20 days post placement) of the study, fecal samples were collected from three pigs per feeder to determine fecal DM. From d 0 to 7, an SBM × bacillus interaction was observed (P < 0.05) for ADFI, where pigs fed high SBM diets had decreased ADFI compared to pigs fed low SBM when bacillus was not in the diet; however, when bacillus was in the diet, SBM level did not affect ADFI. Additionally, pigs fed high SBM had decreased (P < 0.05) ADG and poorer F/G compared to pigs fed low SBM. From d 7 to 21, the SBM × bacillus interaction was observed (P < 0.05) for ADG and F/G, where pigs fed high SBM had increased ADG and improved F/G compared to pigs fed low SBM when bacillus was not in the diet; however, when bacillus was in the diet, SBM level did not affect ADG, and there was a smaller improvement in F/G in pigs fed high SBM compared to those fed low SBM. Pigs fed high SBM had decreased (P < 0.05) ADFI compared to pigs fed low SBM. From d 21 to 42, there was a tendency (P = 0.076) for pigs fed bacillus to have higher ADG compared to pigs not fed bacillus. Overall, the SBM × bacillus interaction was observed (P < 0.05) for F/G, where pigs fed high SBM had improved F/G compared to pigs fed low SBM when bacillus was not in the diet; however, when bacillus was in the diet, SBM level did not affect F/G. For fecal DM, pigs fed high SBM had decreased (P < 0.05) fecal DM compared to pigs fed low SBM. The SBM × bacillus interaction was observed (P < 0.05) for total removals and mortality, where pigs fed high SBM had increased total removals and mortality compared to pigs fed low SBM when bacillus was not in the diet; however, when bacillus was in the diet, SBM level did not affect total removals and mortality. In summary, high SBM had negative effects on phase 1 growth, fecal DM, and removals and mortality, but high SBM improved phase 2 ADG and phase 2 and 3 F/G. When bacillus was not in the diet, high SBM increased removals and mortality; however, when bacillus was in the diet, SBM level did not affect removals and mortality.
Keywords: bacillus; fecal dry matter; growth; nursery pigs; soybean meal